Evaluating the Diagnostic Efficacy of Transvaginal and Transabdominal Ultrasound in the Detection and Characterization of Ovarian and Uterine Masses - Rizwana Rehman Bazai, Shazia Saeed, Roona Khan, Sajida Ghilzai, Nazia Khan, Palwasha Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: This study aimed to compare the diagnostic performance of transabdominal ultrasound (TAUS) and transvaginal ultrasound (TVUS) in the evaluation of ovarian and uterine masses in a resource-constrained Pakistani setting in a prospective observational study. Limited diagnostic resources and high clinical burden require the use of optimal imaging strategies for improved patient outcome. Methodology: The study was conducted from January to December 2022 at Shaikh Hospital and Bolan Medical College Hospital, Quetta, Pakistan. Fifty consecutive female patients aged 18 years or older with pelvic pain, abnormal vaginal bleeding, or palpable pelvic mass were enrolled. Both TAUS (2–5 MHz transducer) and TVUS (5–9 MHz transducer) were performed on each patient on the same day. Lesion size, shape, margin definition, internal echotexture, composition, and vascularity were detailed imaging markers recorded. Sensitivity, specificity, positive and negative predictive values, and overall accuracy were compared to histopathological or composite clinical diagnoses. Paired comparison of malignant lesion detection was done using the McNemar test and Cohen’s kappa statistic was used to measure interobserver agreement. Results: The mean age of the patients was 38.2 ± 12.1 years, 75% of the lesions were found to be benign, and 25% were malignant. TVUS showed a better diagnostic performance than TAUS, with a sensitivity of 90% versus 80% and an overall accuracy of 90% versus 85%. The difference was statistically significant in favor of TVUS (p = 0.04), and the interobserver agreement was good (κ = 0.78). Discussion: TVUS is found to be more accurate than TAUS in the diagnosis of ovarian and uterine masses and should be incorporated into routine clinical protocols in resource-limited environments. Keywords: Transvaginal ultrasound, Transabdominal ultrasound, Ovarian mass, Uterine mass, Diagnostic accuracy, Gynecological imaging, Resource-limited settings, Pakistan, Sensitivity, Specificity.